Comparison of Airborne Flora Before and After Learning Activities in Skill Lab and Tutorial Rooms at the Faculty of Medicine, Yarsi University, and a Review From an Islamic Perspective - Lintang Ramadhani, Himaulya; Irmawati Purbo Astuti, Ike; Djannatun, Titiek (Jurnal Indonesia Sosial Sains, 2026)
Indoor Air Quality (IAQ) significantly affects health and concentration in educational environments. Factors such as learning activities, population density, and ventilation systems influence the presence of airborne microorganisms. This research aims to compare the airborne flora before and after learning activities in the Skill Lab and Tutorial rooms at the Faculty of Medicine, YARSI University, and to analyze the findings from an Islamic perspective. A descriptive qualitative–quantitative method was applied, with 20 samples collected using the settle plate method on Nutrient Agar media. Samples were incubated at 35–37°C for 48 hours, and the bacterial colonies were then counted (CFU) and identified using Gram staining. The results show that the number of airborne microorganisms in five Skill Labs and five Tutorial rooms remained below the standard threshold for air quality (<700 CFU/m³). However, there was a noticeable increase in the number of colonies after learning activities, with the lowest value recorded at 0 CFU/m³ and the highest at 13 CFU/m³. This increase is suspected to be related to human activity, density, and mobility during class sessions. Microscopic identification revealed the predominance of Gram-positive Coccus bacteria, with some Gram-negative rods. In conclusion, the number of airborne microorganisms in the Skill Lab and Tutorial rooms at the Faculty of Medicine, YARSI University, is still within the quality standard, although learning activities contribute to an increase in colony numbers. Therefore, optimal management of the room environment is necessary to maintain good air quality.